Plasma Sphingomyelins as Biomarkers for Diabetic Retinal Neurodegeneration: The Maastricht Study - Siddhita A. Jadhav, MSc; Birke J. Benedikter, PhD; Sara B.A. Mokhtar, MSc; Frank C.T. van der Heide, MD, PhD; Govindasamy Kumaramanickavel, MD; Marleen M.J. van Greevenbroek, PhD; Carroll A.B. Webers, MD, PhD; Tos T.J.M. Berendschot, PhD (Ophthalmology Science, 2025)
Objective: Sphingomyelin (SM) may play a role in the early stages of diabetic retinopathy. Early diagnosis of diabetic retinopathy is crucial for preventing the irreversible vision loss associated with this condition. This study aimed to examine the link between SM and key indicators of diabetic retinopathy, namely retinal neurodegeneration, including corneal nerve measures, retinal layer thickness, and mean retinal sensitivity. Understanding these relationships may help identify early biomarkers and therapeutic targets for preventing or slowing the progression of diabetic retinopathy. Design: We used data from the Maastricht Study, a large population-based observational cohort with oversampling of individuals with type 2 diabetes mellitus (T2DM). Subjects: In this study, SM levels were examined across 3 study groups: (1) individuals with normal glucose metabolism; (2) prediabetes; and (3) T2DM. Methods: Fasting plasma SM levels were measured using the nuclear magnetic resonance platform from Nightingale Health. Main Outcomes and Measures: Linear regression analysis was conducted to assess the link between total plasma SM (determinant) and indicators of retinal neurodegeneration (outcomes), including corneal nerve measures, mean retinal sensitivity, and retinal thickness, while adjusting for potential confounders affecting SM metabolism. Results: Among the 3598 individuals examined, the average plasma levels of total SM were significantly lower in individuals with T2DM (P < 0.001) than those with prediabetes and the control group, even after stratification by lipid-modifying medication usage. In regression analysis, after full adjustment, lower levels of SM were associated with reduced mean retinal sensitivity: β (95% confidence interval) for the right eye (n = 1934), 0.088 (0.012, 0.164) and for the left eye (n = 1925), 0.111 (0.033, 0.189). However, no significant correlations were found with other indicators of retinal neurodegeneration. Conclusions: Lower levels of plasma SMs were linked to reduced retinal sensitivity in individuals with diabetes, indicating their involvement in early neurodegenerative alterations in the diabetic retina. These findings suggest that SMs could be explored as potential biomarkers for detecting diabetic retinal neurodegeneration at an early stage of diabetes. However, further research is essential to clarify the biological pathways involved and to evaluate the effectiveness of SMs as clinical biomarkers. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.